TEKNIK TEXT MINING UNTUK MENGANALISIS WACANA MODERASI AGAMA: WAWASAN DARI RUANG DIGITAL INDONESIA - Tabroni, Roni; Reza Shaker, Ardekani; Yunani, Ahmad (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2024)
The socialization of religious moderation discourse in the digital space requires an effective strategy to engage the Indonesian populace. This study aims to understand the patterns and forms of religious moderation discourse in the Indonesian digital space from 2020 to 2023 and to assess the effectiveness of text mining techniques in this context. A mixed-method approach, combining digital humanities with quantitative text mining and qualitative discourse analysis, was employed to analyze the discourse on religious moderation. The findings indicate that the discourse is dominated by the term